Management of primary hepatic pregnancy: A case report - Yusuf Mohammed Yusuf; Gulilat Tigiye Endeshaw; Berhanu Mohammed Shifa; Biniyam Afework Abate; Ashenafi Aberra Buser; Mohammednur Ali Mohammed; Shimelis Ayalew Yimer; Yabets Tesfaye Kebede; Bekri Delil Mohammed (Case Reports in Women's Health)
Hepatic pregnancy, an exceedingly rare subtype of abdominal ectopic pregnancy, remains clinically challenging due to its infrequency, diverse presentations, and diagnostic difficulties. We report the clinical course, diagnostic journey and treatment of a woman with a primary hepatic pregnancy.The patient presented with acute pain in the right hypochondrium and vomiting. Imaging revealed a peripheral hypodense gestational sac within the right hepatic lobe containing a fetus with heart pulsations, as well as peritoneal fluid and pelvic collection. Following administration of mifepristone, the patient underwent a laparotomy, and expelled a developed fetus. Hepatic resection utilizing the Pringle maneuver was performed, and methotrexate was administered postoperatively. The patient had a stable recovery and vital signs and was discharged two days after surgery.This case highlights the diagnostic and management challenges of hepatic pregnancy, and emphasizes the need for heightened clinical suspicion and thorough evaluation. By sharing the experience, we aim to contribute insights to guide the diagnosis and management of similar cases.